Effect of Adding Brewers’ Spent Grains to The Substrate of Oyster Mushroom Pleurotus florida on its Productivity and Quality (Damascus University Journal for the basic sciences, 2026)
This research was aimed to study the effect of adding four concentrations (5, 10,15 and 30%) Brewers’ Spent Grains to oyster mushroom substrate (wheat straw) on productivity and quality of Pleurotus florida. The productivity indicators (yield and biological efficiency) and chemical content (the percentage of protein, total phenols, antioxidant activity (DPPH%) were recorded. The results shown that most of the concentrations of Brewers’ Spent Grains increased productivity and biological efficiency, but high concentrations 30% caused the death of mycelium.However, treatment 15% of Brewers’ Spent Grains was the best compared to the control and other treatments, which increased both productivity (407.03 g/kg wet substrate) and biological efficiency (116.63%). Moreover, adding Brewers’ Spent Grains to the substrate increased the nutritional value of oyster mushroom. Protein and antioxidant activity were the highest at 15% of Brewers’ Spent Grains (32.40 % of dry matter and 63.54 DPPH%). As the result, we recommend that the addition of Brewers’ Spent Grains used in this research has a positive effect on the production and nutritional value of oyster mushrooms on the one hand and for safe disposal of it on the other, thus mushroom farmers can be advised to use it.
Keywords: Oyster Mushroom; Brewers’ Spent Grains; Wheat Straw; Biological Efficiency; DPPH%.